Risk factors for acute exacerbation of interstitial lung disease during chemotherapy for lung cancer: a systematic review and meta-analysis - Wang, Zhen; Bai, Jiayu; Liu, Yujia; Li, Peng; Jiao, Guangyu (Frontiers in Oncology, 2023)
Purpose The aim of this study was to investigate the risk factors for acute exacerbation (AE) of interstitial lung disease caused by chemotherapy for lung cancer. Methods We searched PubMed, Embase, and The Cochrane Library databases from the establishment of each database to April 2023. Eligible studies were included, and the data on risk factors related to AE caused by chemotherapy in interstitial lung disease were extracted. Results A total of 878 articles were retrieved and 21 met the inclusion criteria. The studies included 1,275 patients with lung cancer combined with interstitial lung disease. The results of the meta-analysis showed four significant risk factors for AE of interstitial lung disease, namely age < 70 years (odds ratio [OR]: 1.98, 95% confidence interval [CI]: 1.05–3.72), forced vital capacity (FVC) (MD=-9.33, 95% CI: -13.7–4.97), usually interstitial pneumonia (UIP) pattern on computed tomography (CT) (OR: 2.11, 95% CI: 1.43–3.11), and serum surfactant protein D (SP-D) (SMD: 0.35, 95% CI: 0.03–0.67). Conclusion When patients with lung cancer complicated with interstitial lung disease are aged < 70 years, have a UIP pattern on CT, have lower FVC values, and have higher serum levels of SP-D, chemotherapy should be carried out with care.